2021
DOI: 10.1590/1806-9282.67.01.20200633
|View full text |Cite
|
Sign up to set email alerts
|

Race inequalities in maternal mortality in the city of Rio de Janeiro, Brazil: 2010-2019

Abstract: OBJECTIVE:To analyze the behavior of maternal mortality according to the race/color variable in the city of Rio de Janeiro, Brazil, between 2010 and 2019.METHODS: This is a cross-sectional study that used microdata collected in the Sistema de Informações sobre Mortalidade and Sistema de Informações sobre Nascidos Vivos. Data were disaggregated by race/color and age groups of childbearing age. Pearson's χ 2 test was used to compare the ratio in each category of covariates. In order to explore the differences in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…With regard to the obstetric population, a study carried out in 2020 with 12,556 pregnant and postpartum women with SARS due to Covid-19 in Brazil, showed that deaths from Covid-19 were twice as high in women who called themselves black, when compared to white women [ 28 ]. It is known that in Brazil, racial disparities in maternal mortality existed even before the pandemic, when the number of deaths among black, brown and indigenous women was disproportionately higher [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the obstetric population, a study carried out in 2020 with 12,556 pregnant and postpartum women with SARS due to Covid-19 in Brazil, showed that deaths from Covid-19 were twice as high in women who called themselves black, when compared to white women [ 28 ]. It is known that in Brazil, racial disparities in maternal mortality existed even before the pandemic, when the number of deaths among black, brown and indigenous women was disproportionately higher [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding ethnic-racial aspects, studies have shown the occurrence of inequities in the profile of maternal mortality, with a higher frequency among Black, mixed-race and indigenous women. 22 ),( 23 The Birth in Brazil Survey, conducted with adolescents in postpartum period in 2011, observed a higher proportion of unfavorable conditions among Black women: lower adequacy of prenatal care, routine tests were not performed during pregnancy, low frequency of guidelines on pregnancy and childbirth, and greater need to seek health care during the labor process. 24 …”
Section: Discussionmentioning
confidence: 99%
“…3 Ethnoracism is a structural determinant of health, 4 imposing barriers to accessing resources and opportunities in hiring, remuneration, adequate housing, and food security. 5 Institutional racism imposes barriers to access and quality services, such as daycare centres, schools, and health care, including discriminatory practices within health services and other institutions. 6 Effects of institutional racism influencing maternal and child health outcomes include the risks of pregnancyrelated complications resulting in maternal or child health problems and deaths, barriers to access to antenatal, delivery, and postnatal care, and services which are unfavourable to Black, Brown or Mixed race, and Indigenous mothers and children in Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…6 Effects of institutional racism influencing maternal and child health outcomes include the risks of pregnancyrelated complications resulting in maternal or child health problems and deaths, barriers to access to antenatal, delivery, and postnatal care, and services which are unfavourable to Black, Brown or Mixed race, and Indigenous mothers and children in Brazil. 5,[7][8][9][10] Differences in the odds of child survival among different racial and ethnic groups were found when investigated in previous studies, with lower odds among Black, Brown or Mixed race, and Indigenous children. 11,12 In Brazil, extreme inequality is driven by class, gender, and race or ethnicity, 5 and ethnoracial inequalities in child survival have been documented between 1950 and 2000.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation